2015
DOI: 10.1021/jp512722x
|View full text |Cite
|
Sign up to set email alerts
|

Design Insights for Tuning the Electrocatalytic Activity of Perovskite Oxides for the Oxygen Evolution Reaction

Abstract: Rechargeable metal-air batteries and water electrolyzers based on aqueous alkaline electrolytes hold the potential to be sustainable solutions to address the challenge of storing large amounts of electrical energy generated from solar and wind resources. For these batteries and electrolyzers to be economically viable, it is essential to have efficient, durable and inexpensive electrocatalysts for the oxygen evolution reaction. In this manuscript, we describe new insights for predicting and tuning the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…13 Meanwhile, oxygen reduction reaction (ORR) at the cathode allows the reduction of oxygen to hydroxide ions in alkaline electrolyte with the electrons obtained from the electrochemical oxidation of the metal anode. [14][15] In fact, ORR at the cathode plays the most important part in overall performance including discharge rate and capacity of metal-air battery. The desired cathodic reaction which is often referred as direct 4 electron transfer can be written as follows: [16][17] …”
Section: Introductionmentioning
confidence: 99%
“…13 Meanwhile, oxygen reduction reaction (ORR) at the cathode allows the reduction of oxygen to hydroxide ions in alkaline electrolyte with the electrons obtained from the electrochemical oxidation of the metal anode. [14][15] In fact, ORR at the cathode plays the most important part in overall performance including discharge rate and capacity of metal-air battery. The desired cathodic reaction which is often referred as direct 4 electron transfer can be written as follows: [16][17] …”
Section: Introductionmentioning
confidence: 99%
“…They not only serve to decompose peroxide during oxygen reduction, but are also catalytically active for the oxygen evolution reaction. [32][33] The best-studied perovskites (general formula ABO 3 ) are the cobaltates, nickelates and manganates, which contain the rare-earth elements (lanthanum and neodymium) in the A site of the perovskite. To improve the conductivity of these perovskites, the A site is often substituted partially with calcium, barium or strontium.…”
Section: (1)mentioning
confidence: 99%
“…Mixed-metal perovskites of the type AA´(BB´)O 3 (e.g., La 0.6 Ca 0.4 Co 1−x Mn x O 3 ) present the opportunity to tune the activity for oxygen reduction and oxygen evolution by changing the composition of the metals. 32,34 The onset potential for oxygen reduction on perovskite-carbon composites is in the range of 0.0 to −0.1 V vs. the mercury/ mercuric oxide (MMO) electrode. 26 This range of potentials is 0.4 V negative to the standard reduction potential for the oxygen reduction reaction.…”
Section: (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…An example of this is lanthanum cobalt oxide (LaCoO 3 ), in which partial substitution of lanthanum (3+) by calcium (2+) results in cobalt with varied oxidation states (2+, 3+, 4+), increased electrical conductivity and generation of oxygen vacancies. Several substitutions causing varied electrochemical performances have been reported for LaCoO 3 , [13][14][15][16][17] using Ca or Sr in the A site and Mn, Fe, Ni, Cu, among others, in the B site. Molecular orbital principles showed that an optimized catalyst for OER in alkaline media can be a perovskite containing cobalt and iron as the transition metal ions.…”
mentioning
confidence: 99%